Oral toxicity of chemical substances found in Dimorphandra mollis (Caesalpiniaceae) against honeybees (Apis mellifera) (Hymenoptera: Apidae) - Cintra, Priscila [UNESP]; Malaspina, Osmar [UNESP]; Bueno, Odair Correa [UNESP]; Petacci, Fernando; Fernandes, João B.; Vieira, Paulo C.; Da Silva, Maria F.G.F. (My University, 2005)
Dimorphandra mollis is a characteristic plant from Brazilian saP vanna-like vegetation. The pollen of this species could be toxic to bees and the objective of the present investigation was to study the toxicity of methanolic extracts obtained from the flowers, peduncles and stem bark of D. mollis to Apis mellifera workers. For the study, the extracts were incorporated into the diet of the bees for later evaluation of mortality rates. The substances isolated: neoisoastilbin, catechin, astilbin and tannins were tested on adult workers and only catechin did not cause toxic effects. The data obtained in the toxicity bioassays were analyzed statistically by Log Rank test and all methanolic extracts showed significant (p<0.0001) toxic effects. Astilbin is also the major component of pollen grains, and is probably responsible for honeybee mortality during blooming periods.
Keywords: Barbatimão; Astilbin; Catechin; Neoisoastilbin; Toxicology; Apidae; Apis mellifera; Apoidea; Caesalpinioideae; Dimorphandra mollis; Hymenoptera